Subacute dermal toxicity study of bensulfuron-methyl in Sprague-Dawley rats. (3rd April 2022) - Cai, Tuo; Wen, Sihui; Yang, Xiuhong; Yu, Xiaowei; Chen, Jianfeng; Wu, Jun; Zhang, Lina; Zhan, Lichao; Luo, Kaiwen; Yi, Jiping; Zhu, Xiaochuan; Nie, Yunfeng
Abstract: Background: Bensulfuron-methyl has recently attracted attention given its widespread use as an herbicide in crops, especially its transdermal safety. However, no dermal toxicity study of this pesticide to mammals has been reported. The present study aims to investigate subacute dermal toxicity of bensulfuron-methyl following repeated doses exposure. Methods: Forty-eight Sprague-Dawley rats were randomly divided into four groups: a normal control group and bensulfuron-methyl groups of different concentrations (250, 500, 1000 mg/kg.bw/day). The rats were topically applied with the substance dermally for 6 h per day for 28 days. At the end of the experiment, all rats were monitored for any changes in their hematological, biochemical parameters, and pathological and histological sections. Results: There were no statistically significant differences ( P  ≥ 0.05) in the hematological parameters and biochemical parameters. The pathological histological results of rats in the control and the highest concentration group showed no significant abnormalities. The NOAEL of subacute dermal toxicity study was found to be 1000 mg/kg.bw/day in both female and male rats. Conclusion: The result indicated that bensulfuron-methyl is probably safe for humans as a pesticide.